Long quasi-periodic oscillations of sunspots and small-scale magnetic structures - Smirnova, Victoria (fi=Turun yliopisto|en=University of Turku|, 2020)
This thesis presents the investigations and the interpretation of long quasi-periodic oscillations with periods more than 30 minutes observed in the magnetic field of sunspots, as well as, at millimeter radio emission nearby sunspots. Additionally, the same phenomenon of long quasi-periodic oscillations was studied for the magnetic field of smallscale magnetic structures related to the facular knots observed in solar chromosphere. Two different methods of data processing are used to obtain the quasi-periodicity. The first method is the traditional Wavelet transform, and the second method is the Empirical Mode Decomposition (EMD). Firstly, long quasi-periodic oscillations of the millimeter (37 GHz) radio emission of active regions above sunspots were obtained with periods in the interval of 1-5 hours. The same periods were obtained for the magnetic field of the sunspots observed in these active regions. The time-lags between the magnetic field oscillations and the millimeter radio emission oscillations were derived in the interval of 15-30 minutes. The interpretation of observed oscillations and lags was done by using the so-called "three-fluxes" model. Secondly, the non-stationary long quasi-periodic oscillations of the magnetic field of facular knots were obtained with periods in the interval of 30-260 minutes. The interpretation of the observed periodicities was done by using the modelling of oscillations of the system with a time-varying rigidity. Three-fluxes model together with the shallow sunspot model gave the physical interpretation of the observed long quasi-periodic oscillations of the millimeter radio emission and the magnetic field of sunspots. Hydrostatic rebuilding of physical parameters of millimeter radio source modulated by the oscillations of the magnetic field of a sunspot as a whole describes the observed lags between the time series in the interval of 15-30 minutes, when the radio emission delay relatively to the magnetic field variations. In the other case, the shallow sunspot model could not be directly used to provide the interpretation of the observed oscillations of facular knots. This requires a number of physical parameters, that have not been observed yet (the analog ofWilson’s depression of the sunspot, the lower boundary of the facular knot). In this case, the model of the facular knot as the system with the time-varying rigidity is in good agreement with the observed dynamics of these objects, and it could be the first step to the new analytical model of the facular knot that will consider the dynamical properties of this small-scale object.

Väitöskirja käsittelee Auringon pitkien, yli 30 minuutin mittaisten kvasijaksollisten värähtelyjen havaintoja ja niiden tulkintaa. Värähtelyjä havaittiin auringonpilkkujen magneettikentässä ja millimetriaalloilla auringonpilkkujen lähellä. Lisäksi tutkittiin pitkiä kvasijaksollisia värähtelyjä magneettikentän pienen skaalan rakenteissa. Nämä rakenteet liittyvät Auringon kromosfäärissä havaittujen kirkkaiden kohtien, ns. fakuloiden solmukohtiin. Työssä käytetään kahta erilaista analyysimenetelmää kvasijaksoisuuden havaitsemiseksi: tavallista aallokemuunnosta sekä empiiristä moodihajotelmaa (EMD). Työssä havaittiin millimetrialueella (37 GHz) radiosäteilyn pitkiä kvasijaksollisia värähtelyjä Auringon aktiivisilta alueilta auringonpilkkujen yläpuolella. Näiden värähtelyjen jaksonajat ovat 1-5 tunnin väliltä. Samat jaksot havaittiin aktiivisilla alueilla havaittujen aurinkopilkkujen magneettikentän värähtelyille. Aikaviiveeksi magneettikentän värähtelyjen ja radiosäteilyn millimetriaaltojen värähtelyjen välillä saatiin 15-30 minuuttia. Havaittujen värähtelyjen ja viiveiden tulkinta tehtiin ns. kolmivuomallilla. Työssä havaittiin myös fakuloiden solmujen magneettikentän epävakaita pitkiä kvasijaksollisia värähtelyitä, joiden jaksonajat olivat 30-260 minuuttia. Fakuloiden solmujen havaittujen jaksonaikojen tulkinta tehtiin käyttämällä värähtelymallia, jossa systeemin jäykkyys vaihteli ajallisesti. Auringonpilkkujen millimetriaaltohavaintojen ja auringonpilkkujen magneettikentän havaintojen pitkien kvasijaksollisten värähtelyjen fysikaalinen tulkinta perustui kolmivuomallin ja matalan aurinkopilkkumallin yhdistelmään. Auringonpilkkujen magneettisten muutosten moduloima millimetriradiolähteen fysikaalisten parametrien hydrostaattinen rekonstruktio kuvaa hyvin aikasarjojen välisiä havaittuja viiveitä alueella 15-30 minuuttia. Fakuloiden solmujen värähtelyiden tapauksessa samaa mallia ei voitu suoraan käyttää, sillä tämä vaatisi tietoa useista fysikaalisista parametreista, joita ei ole vielä havaittu (Wilsonin auringonpilkkualeneman analogia, fakuloiden solmun alareuna). Tässä tapauksessa fakuloiden solmun värähtelymalli, jossa järjestelmällä on ajasta riippuva jäykkyys, on sopusoinnussa solmujen havaitun dynamiikan kanssa. Työ muodostaa ensimmäisen askeleen kohti uutta analyyttistä fakulasolmumallia, joka ottaa huomioon systeemin dynaamiset ominaisuudet.